FINE MOTOR SKILLS THROUGH THE IMPROVEMENT OF DECORATION (Action Research Group of RA B4. Al-Huda Bengkulu City Year 2015/2016) - Tri Juli Hajani (Jurnal Perspektif Pendidikan, 2017)
This action research aims to describe the process of learning outcomes through the activities of the decor in an effort to improve fine motor skills of children. The research model used is Kemmis and Taggart to the subject of research as 12 childrens. The collected data used in this action research is interview, observation and documentation, while the data analysis technique used is the analysis of qualitative and quantitative data. Results of action research shows that the increase in the fine motor skills of children in group B4 RA. Al-Huda is conducted through dekorasi.TCP fine motor skills of children in pre-cycle activities amounted to 37.08;on the activities of the first cycle of 61.17; and on the activities of the second cycle of 80.08.